THE INFLUENCE OF TEACHER CREATIVITY IN MANAGING LEARNING ON MOTIVATION STUDENT LEARNING - Hastuti (CV. Fahr Publishing, 2024)
This research is quantitative research with an ex post facto type of research, the research location is located in Cinnong Village, Sibulue District, namely SMA Negeri 12 Bone and the data sources are economics subject teachers and students in class XI IPS 1 and XI IPS 2. Data collection process, researchers used observation, documentation and questionnaires with follow-up of the data using descriptive analysis techniques with validity and reliability testing stages, as well as hypothesis testing with simple regression equations and t tests (partial). The results of research using questionnaires related to teacher creativity and student learning motivation, the validity test carried out on variable table 0.05. In variable Y, the sig value of each item is the highest value 0.042 < 0.05 from number 12 and the calculated r value > r table with the lowest value 0.271, r table 0.05, namely 0.260. The reliability test for In hypothesis testing, the constant number 154,448 means that if there is no variable .05 with the conclusion that H0 is rejected. In the t test the calculated t value is -4.166 with df = n-2 (10 – 2 = 8) with a value of 1.860 which has a significant effect.